EFFECTS OF BIRTH TYPE ON FATTENING PERFORMANCE AND CARCASS CHARACTERISTICS OF D’MAN LAMBS IN SOUTHWESTERN ALGERIAN OASES - Boubekeur Abderrahmen; Souddi Mohammed; Benidir Mohammed (Natural Resources and Sustainable Development)
The current study investigated the fattening performance and carcass characteristics of D'man lambs born of different litter sizes. The data was collected at INRA's Adrar experimental station. Eighteen lambs, single-born, twin, and triplet at approximately six months of age, and 20 kg of weight were raised for 80 days under similar conditions. Lambs were slaughtered at an average age of 262 days, and carcass characteristics were evaluated. The final live weight of single-born, twin, and triplet lambs’ groups were 38.08, 33.33, and 28.53 kg (P < 0.001), respectively, and for daily live weight gain were 0.225, 0.175, and 0.121 Kg (P < 0.001), respectively. Single-born lambs had the lowest feed conversion efficiency and feed cost compared to twins and triplets (P < 0.001). Hot carcass weight was 19.1, 16.9, and 13.5 kg (P < 0.001) in single-born, twin, and triplet lambs’ groups, respectively. Consequently, the lungs and heart, kidneys, head, paws, and skin weights of single-born lambs were higher than twins and triplets. However, twin lambs had the best fat score, and the differences between the three groups of lambs in terms of mesenteric fat weights were statistically significant (P < 0.05). In conclusion, birth type affected the fattening performances and carcass characteristics of D'man lambs. Indeed, the fattening performance and slaughter characteristics of single-born D'man lambs were